PENINGKATAN KEAMANAN ALGORITMA VIGENÈRE DENGAN PROTOKOL TIGA LANGKAH TANPA PENDISTRIBUSIAN KUNCI - Siahaan, Andysah Putera Utama (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2023, 2023)
In computer networks, information exchange is common. The information transmitted can be confidential or ordinary. However, when sending confidential information, there are often concerns about its security. Senders tend to worry that the information sent will be stolen, especially if it contains confidential data. In order for the information to be read correctly, the sender and receiver must know the key or password. However, sending keys is also an important concern because if it falls into the wrong hands, the data and information contained in the file can be read easily. Therefore, key exchanges should be avoided and one of the techniques that can be used to avoid them is the Three Step Protocol scheme. This scheme allows the sender and receiver to encrypt and decrypt using their respective keys without having to exchange keys. The Three-Step Protocol is a mechanism that involves two algorithms in the cryptographic process, the Vigenère Algorithm. By implementing the Three-Step Protocol scheme, it can improve data security.